CAPITAL MARKET DEVELOPMENT AND ECONOMIC GROWTH IN NIGERIA (American International Journal of Economics and Finance Research, 2021)
The motivation behind this study is to experimentally look at the connection between capital market improvement and monetary development in Nigeria. The examination investigated the Central Bank of Nigeria quarterly information from 1981Q1 to 2017Q4 with the E-sees programming bundle (variant 9.0). The Vector Auto Regression (VAR) procedure was utilized to investigate the information, while theory testing depended on the Block Exogeneity Wald test. The predetermined models included stationarity tests, diminished structure VAR gauge, and primary examination. The Augmented Dickey-Fuller Test demonstrates that the examination factors are fixed at first contrast or I(1). The VAR establishes plot corresponding to unit circle demonstrates that our predetermined diminished structure VAR models are steady. The Lagrange Multiplier (LM) symptomatic tests demonstrate that our predetermined VAR models are effectively indicated. The p-esteem shows that market capitalization proportion is critical in clarifying varieties in financial development (p = 0.0205). Notwithstanding, the worth of stock proportion and banking framework capitalization proportion is not huge in deciding the Real Gross Domestic Product in Nigeria. All in all, capital market advancement in Nigeria is worked with by vigorous market capitalization. Nonetheless, it is restricted by diminishing volume of stock and lessening banking framework capitalization. It is suggested that the monetary area ought to take on forceful capital market drives and vigorous monetary development approaches to support financial development in an arising economy.